Pollen morphology of Senecio L. and Iranecio B. Nord. (Asteraceae: Senecioneae) in Iran - Eftekharian, Rosa; Sheidai, Masoud; Attar, Farideh; Noormohammadi, Zahra (Acta Biologica Szegediensis, 2017)
The genus Senecio L. is one of the largest genera in the family Asteraceae. The number of taxa included in this genus is 1250. Pollen morphology has proved useful in the systematics of Asteraceae as well as in that of some of its genera and species. The pollen morphology of 16 taxa of the genus Senecio and Iranecio was investigated in detail by scanning electron microscopy (SEM). Examination showed pollen grains to be isopolar and radiosymmetric, prolate spheroidal. The close relationships are observed between the species of the section Quadridentati and the genus Iranecio. The species of the section Jacobaea showed a palynological overlap with the section Senecio. The results indicate that the palynological characters of the genus Senecio are valuable for taxonomic applications and are useful for classification.